2014
DOI: 10.1103/physrevb.89.205432
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and incoherent thermal transport in nanomeshes

Abstract: Coherent thermal transport in nanopatterned structures is a topic of considerable interest, but whether it occurs in certain structures remains unclear due to a poor understanding of which phonons conduct heat. Here, we perform fully three-dimensional, frequency-dependent simulations of thermal transport in nanomeshes by solving the Boltzmann transport equation with an efficient Monte Carlo method. From the spectral information in our simulations, we show that thermal transport in nanostructures that can be cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 40 publications
4
106
1
1
Order By: Relevance
“…In practice, these pore-edge defects will slightly expand the effective pore diameter in phonon MC simulations. 32 Assuming diffusive phonon scattering by pore edges, k L can be predicted using the kinetic relationship by modifying a)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, these pore-edge defects will slightly expand the effective pore diameter in phonon MC simulations. 32 Assuming diffusive phonon scattering by pore edges, k L can be predicted using the kinetic relationship by modifying a)…”
Section: Introductionmentioning
confidence: 99%
“…10,11,31,32,35 Other k L predictions are based on the numerical 6,7,36,37 and analytical 38,39 solutions of the phonon Boltzmann transport equation (BTE). However, these studies are still complicated and cannot be used for the thermal analysis of general samples with varied porous structures.…”
Section: Introductionmentioning
confidence: 99%
“…32 suggested that it was possible to obtain thermal conductivity close to the amorphous limit with truly nanoscale features. More recent theory, 9,10 following the publication of data on nanostructures, has revisited the Boltzmann transport simulations while considering frequency dependent scattering rates. These are discussed further in Sec.…”
Section: Sub-continuum Phonon Transportmentioning
confidence: 99%
“…The most detailed consideration of transport in periodic structures till date involves modeling phonons through either atomistic simulations [23][24][25] or tracking their trajectories through Monte Carlo simulations. 9,10 We review basic phonon scattering physics here and discuss specific calculations later in Sec. VI.…”
Section: Sub-continuum Phonon Transportmentioning
confidence: 99%
See 1 more Smart Citation